Screening Neoliberalism. Transforming Mexican Cinema, 1988-2012 - Baquero-Pecino, Álvaro (Imagofagia, 2021)
Sobre Sánchez Prado, Ignacio M. Screening Neoliberalism. Transforming Mexican Cinema, 1988-2012, Nashville, Tennessee: Vanderbilt University Press, 2014, 291 pp., ISBN:978-0-8265-1965-8.